2015
DOI: 10.1039/c4tx00060a
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of the intracellular Zn2+level by 2-n-octyl-4-isothiazolin-3-one in rat thymocytes: an involvement of a temperature-sensitive Zn2+pathway

Abstract: High amounts of 2-n-octyl-4-isothiazolin-3-one (OIT), an antimicrobial, are found in wet polyvinyl alcohol towels with cooling properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…We previously reported that OIT increased intracellular Zn 2+ levels through the activation of a temperaturesensitive Zn 2+ pathway (Zn 2+ influx) in rat thymocytes (Fukunaga et al, 2015). Three μM OIT significantly increased the intensity of FluoZin-3 fluorescence (Fig.…”
Section: Oit-induced Changes In Intracellular Zn 2+ Levelsmentioning
confidence: 70%
See 2 more Smart Citations
“…We previously reported that OIT increased intracellular Zn 2+ levels through the activation of a temperaturesensitive Zn 2+ pathway (Zn 2+ influx) in rat thymocytes (Fukunaga et al, 2015). Three μM OIT significantly increased the intensity of FluoZin-3 fluorescence (Fig.…”
Section: Oit-induced Changes In Intracellular Zn 2+ Levelsmentioning
confidence: 70%
“…High concentrations of OIT have been detected in some household products (Nakashima et al, 2000;Aalto-Korte et al, 2007;Kawakami et al, 2014). In our previous study (Fukunaga et al, 2015), we found that OIT increased membrane Zn 2+ permeability through the activation of the temperature-sensitive Zn 2+ pathway, which resulted in increased intracellular Zn 2+ levels in rat thymic lymphocytes. However, the Zn 2+ -dependent insults that were induced by OIT were not elucidated.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…The chemical structure of noctyl-4-isothiazolin-3-one (OIT), an antimicrobial agent, is similar to that of DCOIT. OIT-induced increases in FluoZin-3 fluorescence are completely abolished by TPEN (Fukunaga et al, 2015). Therefore, DCOIT may increase the intensity of FluoZin-3 fluorescence in a Zn 2+ -independent manner.…”
Section: Possible Mechanism For Synergistic Action By H 2 O 2 and Dcoitmentioning
confidence: 92%
“…It is to be mentioned that Zn 2+ enters rat thymic lymphocytes through a temperature-sensitive pathway. The application of ZnCl 2 significantly increases the (Zn 2+ )i and this phenomenon is completely suppressed in cold condition (Takahashi et al, 2012;Fukunaga et al, 2015). The thymus gland is very active in the pre-adolescent and neonatal periods.…”
Section: Introductionmentioning
confidence: 96%